Speech Act Use in Parenting Style toward Children Self-Esteem in Bad Moms Movie - Wenny Pratiwi; Malikatul Laila (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
The parents become one of the crucial factors in determining children’s character. Their character is influenced by the people around them who have frequently made interaction. Based on Bad Moms movie, the changes of parent’s treatment to their children give an effect in several aspects. The technique of collecting the data is watching and examining the movie which relates to language use in parenting style towards children’s self-esteem. The technique of data analysis was done using descriptive method speech acts theory by Kreidler (1998), parenting style theory by Baumrind (1967) and Maslow’s hierarchy of needs in Shintya (2013). Based on Bad Moms movie, the use of directive utterances in the authoritative parenting style support the hearer to do something, by doing something, the children become independent. The use of directive utterances helps the hearer to reduce miscommunication and improve the effective communication.